Penerapan Hipnotis Lima Jari untuk Menurunkan Tingkat Kecemasan pada Orang Tua di Kelurahan Kalipanpur - Wahyuningsih Wahyuningsih; Niken Sukesi; Rahayu W (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Background: Anxiety is a psychological condition of a person who is full of fear and worry, where feelings of fear and worry about something that is not certain will happen. Anxiety comes from Latin (anxius) and from German (anst), which is a word used to describe negative effects and physiological stimuli One way to overcome anxiety is by using deep breathing relaxation techniques and five-finger hypnosis. Some of the benefits of deep breathing techniques are the psychological benefits of relieving stress is one way to relax the body by concentrating on breathing. Deep breathing can help reduce the severity and frequency of stress-related headache tension, slow the heart rate, low blood pressure and reduce fatigue.The five-finger hypnosis technique is a form of self-hypnosis situation diversion that can cause a relaxation effect, so that it will reduce anxiety, tension, and stress from a person's mind which can affect breathing, heart rate, pulse, blood pressure, reduce muscle tension, strengthen memory, release hormones that can trigger anxiety, and regulate hormones related to stress. Teaching parents who experience anxiety with relaxation, namely 5-finger hypnosis, so that anxiety decreases and the body becomes relaxed. Objective: To provide education to the wider community in the use of five-finger hypnosis therapy to reduce anxiety.Method: used in this PKM activity is to implement the implementation, namely explaining the theory of 5-finger hypnosis, interviewing respondents. Demonstration of 5-finger hypnosis, giving examples first, then demonstrating directly.The results of this community service activity are very useful because they can reduce anxiety and the body becomes relaxed, because usually only using deep breathing. So it will be applied if you experience anxiety, the time can be anytime and anywhere.Conclusion: The implementation of the five-finger hypnosis therapy education went smoothly and the results of increased knowledge were obtained before and after education was carried out on how to use five-finger hypnosis to reduce anxiety. The community is expected to be able to practice how to use five-finger hypnosis when feeling anxious as a form of achievement of this program.